Implementasi Mikrokontroler Sebagai Pengendali Kapasitor Untuk Perbaikan Faktor Daya Otomatis pada Jaringan Listrik - Prasetya, Dana Bagus (Jurnal Semesta Teknika, 2010)
With increasing electricity rates, the demands of efficiency in electric power consumption is a major consideration. Efficient use of electric power is affected by many factors. Among them is the quality of electric power. Power quality is strongly influenced by the use of certain types of expenses that resulted in the decline of efficiency. In the distribution of electric energy there are several problem sencountered include the voltage drop, low cos Î¦, and the loss of power. Load on the network load distribution can be either capacitive or inductive, but in general is an inductive load. If the inductive reactive load the higher the voltage drop will produce a zoom in, zoom power loss, cos Î¦ lower and lower distribution of power capacity. To reduce the inductive reactive power load required capacitive reactive power sources, one of which is to be installed in parallel capacitors. In this study will be designing and manufacturing tools for controlling capacitor banks according to cos Ï m, so that power quality will be better. From the results of this research tool was able to detect the value of voltage, current,and cos Ï. The resulting values of the three sensors is quite good. This tool is able tocontrol the capacitor bank in accordance with the value of cos Ï meters.